Organized Labour, Regional Political Bias and the Canadian Tariff Structure - Jones, J.C.H.; Laudadio, L. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
The authors attempt to determine the impact of organized labour as pressure group on tariff differentials for a cross section sample of industries in Canadian secondary manufacturing.